2009
DOI: 10.1111/j.1365-2672.2008.04030.x
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics ofEpicoccum nigrum, a biocontrol agent against brown rot in stone fruit

Abstract: Aims:  To study the population dynamics of Epicoccum nigrum on peaches and nectarines and to enhance its colonization on fruit surfaces to improve its biocontrol efficacy against brown rot. Methods and Results:  Twelve surveys were performed to study E. nigrum populations and their effect on the number of the pathogenic Monilinia spp. conidia in peach orchards in Spain and Italy between 2002 and 2005. Fresh conidia and five different formulations of E. nigrum conidia were applied three to six times to peach an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 40 publications
2
27
0
1
Order By: Relevance
“…We cannot comment at this stage on the morphospecies, but three of the fungal genera identified, Epicoccum, Trichoderma and Ulocladium, contain mycoparasitic species. Some endophytic Epicoccum species have been screened as potential biocontrol agents of fungal pathogens of diverse crops, including potato, sugarcane and stone fruits (De Cal et al 2009;Lahlali and Hijri 2010;Fávaro et al 2012); whilst Trichoderma is a well known mycoparasitic genus that has been widely used for biocontrol of plant pathogens (Harman 2000; Holmes et al 2004)). Similarly, some Ulocladium species have also generated interest as mycoparasites of plant pathogens, and Kohl et al (1997) reported that Ulocladium atrum is antagonistic to Botrytis disease in onions.…”
Section: Fig 2 Continuedmentioning
confidence: 99%
“…We cannot comment at this stage on the morphospecies, but three of the fungal genera identified, Epicoccum, Trichoderma and Ulocladium, contain mycoparasitic species. Some endophytic Epicoccum species have been screened as potential biocontrol agents of fungal pathogens of diverse crops, including potato, sugarcane and stone fruits (De Cal et al 2009;Lahlali and Hijri 2010;Fávaro et al 2012); whilst Trichoderma is a well known mycoparasitic genus that has been widely used for biocontrol of plant pathogens (Harman 2000; Holmes et al 2004)). Similarly, some Ulocladium species have also generated interest as mycoparasites of plant pathogens, and Kohl et al (1997) reported that Ulocladium atrum is antagonistic to Botrytis disease in onions.…”
Section: Fig 2 Continuedmentioning
confidence: 99%
“…in peaches and nectarines [7], [8], [9], against Sclerotinia sclerotiorum in sunflowers [10] and against Pythium in cotton [11]. Many studies have focused on the ability of this fungus to produce antimicrobial compounds such as epicorazins A–B [12], epicoccins A–D [13], epicoccarines A–B and epipyridone [14], flavipin [15] and epirodins [16].…”
Section: Introductionmentioning
confidence: 99%
“…E. nigrum has been used as a biological control agent on peaches and nectarines orchards against Monilinia spp. [28] and Pythium cotton [29].…”
Section: Discussionmentioning
confidence: 99%